The emergence of splinter factions in intrastate conflict. Issue 1 (2nd January 2020) - Burch, Michael; Ochreiter, Leslie
ABSTRACT: Why do some rebel groups fractionalize during intrastate conflict? The focus of this article is on understanding a particular phenomenon within fragmentation during civil war: the emergence of viable splinter factions. Splinter factions are when a new rebel group emerges from an ongoing violent challenge against the state and concurrently launches their own violent campaign rather than continue to pool resources to mount a more effective fight. In this article, we outline how the organizational characteristics of the original rebel movement can create several conditions in which splinter factions will emerge. Organizational decisions regarding, mobilization, central command, and territorial control creates opportunities for aggrieved members within the coalition to strike out on their own. Support for the theory is found through statistical tests on the internal characteristics of rebel groups demonstrating the importance of rebel group structure in understanding contemporary conflict processes.